CORRELATION BETWEEN VISCOSITY AND DENSITY OF THE JETENGINE FUEL - Лахін, Б.; Терсков, Я. (Science-based technologies, 2010)
In this paper the results of studying the correlation between the jetengine fuel property-viscosity and density aregiven. There are shown review of works by other authors and the experimental results obtained by the authors ofthis paper. There was obtained the stable viscosity-density correlation which allows to develop the calculationmethod for viscosity determination which accuracy sufficient for operating enterprises, and to eliminate theviscosity monitoring in the laboratories of aviation enterprises.